Analisis Pengendalian Persediaan Suku Cadang Menggunakan Metode Economic Order Quantity dan Silver Meal - Bara, Yogi Zefanya Batu; Wahyuda, Wahyuda; Sitania, Farida Djumiati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Spare parts inventory is a crucial component in supporting the smooth operation of mining service companies, one of which is PT. XYZ. The company faces excess inventory of workshop support spare parts, particularly oil filters (21707133, 21707132) and fuel filter (22480372). Data processing begins with a variability test, followed by forecasting, and then inventory calculations using the Economic Order Quantity (EOQ) and Silver Meal (SM) methods. The variability test results indicate that oil filters are static (V<0.25), while fuel filters are dynamic (V≥0.25). Forecasting is conducted using a moving average, with MAPE values of 14%, 13%, and 12% respectively. The results show that the total inventory cost amounted to Rp398,085 or 39% lower than the company’s current policy. The optimal order quantity for fuel filter 22480372 from periods 1 to 12 in succession is 20, 21, 20, 18, 18, 19, 18, 18, 20, 20, 19, and 19.